The Effects of Liposomal Bupivacaine on Long-term Outcomes and Decreasing Immediate Postoperative Opioid Use Following One-level and Two-level Posterior Lumbar Fusions. Issue 1 (16th February 2023) - Gannon, Emmett; Freeman, Matthew; Cornett, Chris; Vincent, Scott; Powers, Sydney; Lyden, Elizabeth
Abstract : Study Design: This is a retrospective observational study. Objective: This study aims to determine the efficacy of liposomal bupivacaine in postoperative analgesia and long-term outcomes in patients undergoing one-level and two-level posterior lumbar fusion. Summary of Background Data: Multiple studies have investigated the use of liposomal bupivacaine in spine surgery with varying results. The potential benefits of its use include decreasing postoperative opioid use, improved pain control, and a shorter hospital stay. Several studies have supported its use in spine surgery with others showing minimal to no benefit. No studies have investigated its possible impact on long-term outcomes. Materials and Methods: A total of 42 patients (22 one-level, 20 two-level) received liposomal bupivacaine injection just before surgical closure and were compared with a historical control group of 42 patients (27 one-level, 15 two-level) that did not receive liposomal bupivacaine. Daily opioid consumption was collected and converted to oral morphine equivalents. Length of stay and daily average pain scores using the visual analog scale were also recorded. In addition, SF-36 bodily pain and physical function outcome measures were collected preoperatively and at 6 months, 1 year and 2 years postoperatively. Results: The liposomal bupivacaine group was found to have a significantly lower total opioid consumption compared with the control group ( P =0.001). The liposomal bupivacaine group was also found to use significantly fewer opioids on the day of surgery compared with the control group ( P <0.0001). There was no significant difference shown in the average visual analog scale pain scores, length of stay, or long-term outcomes between the 2 groups. Conclusions: The use of liposomal bupivacaine in one-level and two-level posterior lumbar fusions shows promise as an adjuvant for postoperative analgesia by decreasing postoperative opioid consumption. With the varying results demonstrated with the utilization of liposomal bupivacaine in spine surgery, further investigation is warranted, namely a larger prospective randomized control study. Level of Evidence: Level III.